Flowers in the attic - Adams, Jeb, 1961-; Swanson, Kristy; Fletcher, Louise; Tennant, Victoria, 1950-; Bloom, Jeffry; Levin, Sy.; Fries, Tom.; Bloom, Jeffrey, 1945-; Andrews, V. C. (Virginia C.).; Image Entertainment (Firm); New World Pictures (Firm); Fries Entertainment (Firm); et al. (Chatsworth, CA Image Entertainment, 2011)
After a tragic accident leaves them fatherless, four children return to their mother's mysterious family mansion hoping for an inheritance. But when they are imprisoned and abandoned by their evil grandmother, the children must survive a nightmare of brutal cruelty, forbidden passion, and a final shocking discovery that will shatter their innocence forever.
Based on the novel by V.C. Andrews.
Originally produced as a motion picture in 1987.
Executive producers, Charles Fries and Mike Rosenfeld.
Jeb Stuart Adams, Kristy Swanson, Louise Fletcher, Victoria Tennant.
MPAA rating: PG-13.
DVD, widescreen (1.85:1) presentation; NTSC; Dolby Digital stereo.
Keywords: Abused children -- Drama; Incest -- Drama; Dysfunctional families -- Drama; Drama; Feature films; Fiction films; Film adaptations